SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMA BUDI MULIA DI TANGERANG - Andri Amico; Mochamad Wahyudi; Sumanto (Jurnal Sistem Informasi, 2014)
Abstract— With growing world of technology, especially Internetbased technologies like Web site where all the desired information can be easily and cheaply obtained. The presence of this academic information system website, is expected to help teachers, students, parents, and communities to obtain actual information about the SMA BUDI MULIA at TANGERANG. In building this system I use support tools with object-oriented methodology is UML because UML supports object-oriented programming languages or OOP (Object Oriented Programming), web applications, PHP and MySQL, while for the photo editor I use Adobe Photoshop CS3 and Adobe Dreamweaver CS3 media to write PHP scripts. Browser, function to view the PHP commands that have been run on a web server. Examples of browsers are: Internet Explorer, Netscape Navigator, Opera, Firefox in this case I use Mozilla Firefox. The system generated from the tools above will be much better in terms of efficiency, effectiveness, reliability and flexibility because UML is an object-oriented programming language. And other tools that are easy to understand because it is easy to learn.